(untitled) (Journal of Plant Disease Sciences, 2025)
This study aimed to assess the efficacy of seven fungicides, each applied at varying concentrations , Below Recommended Concentration, Recommended Concentration and Above Recommended Concentration, against different seed borne fungal pathogens affecting Wheat. The standard agar plate method was used to detect the seed borne fungal pathogens on wheat seeds of 10 different varieties. A total of 7 seed borne mycoflora belonging to 6 genera, out of which 4 genera were pathogenic , (6.75% to 14.50%), (9.50% to 16.00%), (4.25% to 14.25%) and (2.50% to 9.75%) and 2 genera were saprophytic .viz. Fusarium moniliforme Alternaria alternata Bipolaris sorokiniana Curvularia lunata (3.25% to 9.50%), (3.25% to 10.25% and (0.00% to 4.25%) were associated with wheat seeds. The efficacy of seven fungicides were evaluated against pathogenic seed mycoflora isolated from wheat seeds by poisoned food technique. All fungicides taken found to have inhibitory effect on the seed borne mycoflora. The first best fungicide was Carbendazim 12% WP + Mancozeb 63% WP followed by Tebuconazole 5.36% FS and Propineb 70% WP. The results confirmed that as the concentration of fungicides was increased, a gradual decrease in the radial growth of these pathogens were observed in all cases.